Rancang Bangun Sistem Informasi Penjualan Makanan Beku Berbasis Web Menggunakan Framework Laravel - Sandro Alfeno; Muh. Panji Midhat; Muhammad Arkandari (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
To market a product is usually done by offering it to many people you meet or giving brochures. However, if a product that is sold and offered to potential buyers is not everyone's consumptive product, then the marketing must be different. The use of digital media in the current technological era, it is highly recommended to market products as a means of selling such as a sales website. With the waterfall method, which is assisted by a framework such as Laravel, which makes it easier to make websites more neat and structured. With the hope of increasing the percentage of sales and achieving sales targets.